Trap aesthetics in the 2010s in Spain - Ollero Gavín, Alfonso (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
The rise of the Trap phenomenon in Spain seems to have deconstructed the foundations for textual and audiovisual creation at levels of both form and content. The subversion that the phenomenon exerts on the sociocultural and material conditions of the music industry has a reflection in the literary creation that trap artists commodify nowadays. Accordingly, the main aim of this work us to understand how trap poets create evidence for the conditions of late capitalism and produce a literary discourse based on a series of (1) rhetorical mechanisms and (2) topoi trap that help configure a genre of noteworthy variability, but, in essence, committed to the creation of a virtual, millenial, and Gen-Z community.